2021
DOI: 10.1111/mec.15856
|View full text |Cite
|
Sign up to set email alerts
|

Complex histories of gene flow and a mitochondrial capture event in a nonsister pair of birds

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 105 publications
1
23
1
Order By: Relevance
“…3f , Table S3 ). This observation contradicts the hypothesis of mitochondrial introgression, though mitochondrial introgression has previously been reported with negligible signs of nuclear introgression (Good et al 2015 ; Andersen et al 2020 ). Taken together, the mitonuclear discordance can be explained by both post-divergence gene flow and ILS.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…3f , Table S3 ). This observation contradicts the hypothesis of mitochondrial introgression, though mitochondrial introgression has previously been reported with negligible signs of nuclear introgression (Good et al 2015 ; Andersen et al 2020 ). Taken together, the mitonuclear discordance can be explained by both post-divergence gene flow and ILS.…”
Section: Discussioncontrasting
confidence: 59%
“…S4 ). This paraphyly could potentially be attributable to ILS or mitochondrial introgression, and differentiating between these two scenarios remains a challenging endeavor (Holder et al 2001 ; Buckley et al 2006 but see Andersen et al 2020 ). If ILS is responsible for the observed discordance, it would require retention of shared mitochondrial haplotypes between O. t. traillii and O. t. robinsoni .…”
Section: Discussionmentioning
confidence: 99%
“…Mito-nuclear discordance has been increasingly found in phylogeographic studies within and among conspecific populations and closely related species ( Avise et al 2016 ). This intriguing phenomenon may be caused by various biological processes, such as female-linked selection (e.g., Fossøy et al 2016 ), sex-biased dispersal (e.g., Roycroft et al 2019 ), mitochondrial capture through introgression (e.g., Andersen et al 2021 ), and invasions by reproductive parasites (e.g., Wolbachia spp., Arif et al 2021 ). In this study, mito-nuclear discordance was mainly observed in the populations located in the hybrid zone, which suggested that the hybrid populations of NMBT and HLQQ incorporating both the western and eastern genetic components detected by the nuclear data were completely grouped into the eastern lineage based on the mitochondrial data.…”
Section: Discussionmentioning
confidence: 99%
“…Mito-nuclear discordance is being increasingly detected in speciation studies, especially among recently diverged lineages (Andersen et al, 2021;Bonnet et al, 2017;Firneno et al, 2020;Mao & Rossiter, 2020;Toews & Brelsford, 2012). Introgression and incomplete lineage sorting (ILS) are two different processes that mainly caused phenomenon of mito-nuclear discordance.…”
Section: Chinensis and L Oratoria And Underlying Factorsmentioning
confidence: 99%